MARITIME INSECURITY IN SUB-SAHARAN AFRICA AND ITS EFFECTS IN THE ECONOMY OF STATES - Ginga, Fernandes Capitão (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
It seems clear that African leaders are not aware of the maritime dimension of their states, which has led to a subordination of maritime affairs compared to land issues, as it is essential that African states begin to take concrete steps in order to establish, on the continent, a true maritime security and defense architecture, with the aim of making the best use of the opportunities offered by the oceans, in the name of the interests of these States. The approach was possible, using a bibliographic and documentary review, through a qualitative methodology, following a deductive reasoning.